Síndrome de hiper-IgM asociado a colangitis esclerosante y neoplasia vesicular: Caso clínico - Rodríguez G,Cristián (Sociedad Médica de Santiago, 2003)
We report a 11 years old male diagnosed as a X-linked hyper-IgM syndrome that presented with recurrent infections and sclerosing cholangitis and later developed a gallbladder cancer. Immunological evaluation showed decreased levels of serum IgG and IgA with elevated levels of IgM. Study of CD40 ligand expression on mitogen activated peripheral blood mononuclear cells revealed total absence of this marker on T lymphocytes. Molecular analysis detected, in the patient and his mother, a nonsense mutation in exon 1 of the transmembrane segment of the CD40 ligand. He also presented elevation of alkaline phosphatases and mild elevation of liver enzymes. Liver biopsy demonstrated the presence of idiopathic sclerosing cholangitis. The patient was started on monthly IVIG therapy at 400 mg/kg, as well as ursodeoxycholic acid and vitamin E, with normalization of his IgG and IgM levels a decrease in the incidence of infections and normalization of liver function. Three years after diagnosis, we detected the presence of polyps inside the gallbladder that were reported at biopsy as adenocarcinoma. He underwent hepatic bisegmentectomy (VI B-V) and local lymphadenectomy (Rev Méd Chile 2003; 131: 303-8).